2014
DOI: 10.1002/anie.201405982
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative to the Classical α‐Arylation: The Transfer of an Intact 2‐Iodoaryl from ArI(O2CCF3)2

Abstract: The α-arylation of carbonyl compounds is generally accomplished under basic conditions, both under metal catalysis and via aryl transfer from the diaryl λ(3)-iodanes. Here, we describe an alternative metal-free α-arylation using ArI(O2CCF3)2 as the source of a 2-iodoaryl group. The reaction is applicable to activated ketones, such as α-cyanoketones, and works with substituted aryliodanes. This formal C-H functionalization reaction is thought to proceed through a [3,3] rearrangement of an iodonium enolate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…Completing the last corner of the reactivity "square" shown in Figure 1, in a 2014 report Vallribera, Shafir and coworkers described a reaction between phenyliodine bis(trifluoroacetate), PIFA, and a range of activated ketones. 22 Under acidic conditions, such combination gave rise to α-arylketones with iodine retained ortho to the new C-C bond. The initial work involved the arylation of cyclic β-diketones and cyclic β-ketoesters, with the coupling products produced in moderate yields (Scheme 21).…”
Section: Scheme 18 Redox α-Arylation Of Amides By Maulide Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Completing the last corner of the reactivity "square" shown in Figure 1, in a 2014 report Vallribera, Shafir and coworkers described a reaction between phenyliodine bis(trifluoroacetate), PIFA, and a range of activated ketones. 22 Under acidic conditions, such combination gave rise to α-arylketones with iodine retained ortho to the new C-C bond. The initial work involved the arylation of cyclic β-diketones and cyclic β-ketoesters, with the coupling products produced in moderate yields (Scheme 21).…”
Section: Scheme 18 Redox α-Arylation Of Amides By Maulide Et Almentioning
confidence: 99%
“…Furthermore, the synthesis of the spiroxindole 84 from the α-(iodoaryl) ketones 74 (Scheme 24) relied on an intramolecular Cu-catalyzed Goldberg-type cyclizative C-N bond formation. 22 In 2015 Shafir et al showed that an intramecular cross-coupling can be combined with ring opening to give a series of interesting polar building blocks (Scheme 31). Thus, while basic treatment of the 5-membered cyclic dione 91 afforded the linear carboxylic acid 106 bearing a 2-iodophenyl substituent, conducting the same reaction in the presence of catalytic CuI/Fe2O3 led to a cross-coupling/ring opening sequence and a new benzophenone carboxylic acid 107.…”
Section: Bmentioning
confidence: 99%
“…20 Cyclic b-ketoesters and b-diketones afforded the a-(2-iodoaryl) derivatives in moderate yields. Particularly efficient was the arylation of a-cyanoketones, tolerating even substituted iodoaryl derivatives.…”
Section: Arylation Of Ketonesmentioning
confidence: 99%
“…[1,2] Prior to and following these advances,u seful transition-metal-free a-arylation processes have been developed that involve stoichiometric reactions of enolate anions (or equivalents) with electrophilic aromatic derivatives of Bi V , [3] Pb IV , [4] I(III), [5] S(IV), [6] or benzyne. [1,2] Prior to and following these advances,u seful transition-metal-free a-arylation processes have been developed that involve stoichiometric reactions of enolate anions (or equivalents) with electrophilic aromatic derivatives of Bi V , [3] Pb IV , [4] I(III), [5] S(IV), [6] or benzyne.…”
mentioning
confidence: 99%